On the Covariance Structure of Earnings and Hours Changes - Abowd, John M.; Card, David (Econometrica, 1989)
This paper presents an empirical analysis of changes in individual earnings and hours ov&r time. Using longitudinal data from three panel surveys, we catalogue the main features of the covariance structure of changes in earnings and hours. We then present an interpretation of these features in terms of both a life-cycle labor supply model and a fixed-wage labor contract nDdel. Our major findings are: (1) there is a remarkable similarity in the covariance structure of earnings and hours changes across the three surveys; and (2) apart from simple measurement error, the major component of variance in earnings and hours affects earnings and hours equi-proportionately.